The Effectiveness of Problem-Based Learning Assisted by EdPuzzle on Students’ Critical Thinking Skills - Mayang, Gendhis Cikal; Efendi, Agus; Taufik Prakisya, Nurcahya Pradana (Universitas Sebelas Maret, 2021)
This research aims to determine the differences in students’ critical thinking skills between the class that applies problem-based learning model through Edpuzzle and the class that applies expository learning model. The method used is quantitative quasi-experimental design using pre-test and post-test control. The sample of this research was participated by 66 students. They were selected by applying the technique of cluster random sampling. The data was obtained from the result of pre-test and post-test based on the indicator of critical thinking skills. The result showed that there were differences and an increase in the critical thinking skills of students who applied the problem-based learning learning model assisted by edpuzzle compared to the expository model It is proven by the result of the 1st hypothesis test through t-test which the post-test result shows the score of 0,014, which means the score is less than the error level of 0,05. Therefore, it can be concluded that both of the classes have significant differences (H0 is rejected). On the other, the 2nd hypothesis test that used the gain test indicates the score of 0,41 for the experimental class and the score of 0,28 for the control class, which means there is a significant increases in the critical thinking skills of both classes.